2016
DOI: 10.1002/mrd.22742
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of melatonin on bovine sperm characteristics and subsequent in vitro embryo development

Abstract: We aimed to investigate the effect of melatonin on bovine frozen-thawed semen and its impact on fertilization outcome. Plasma membrane integrity, mitochondrial activity, acrosome integrity, and levels of intracellular reactive oxygen species (ROS) were measured in spermatozoa treated with different concentrations of melatonin. Melatonin-treated spermatozoa were then used for in vitro fertilization, followed by analysis of subsequent embryo development and the expression of apoptosis- and antioxidant-related ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 37 publications
7
36
1
1
Order By: Relevance
“…The data obtained regarding sperm motility are in accordance with Ashrafi et al, (), Cheuqueman et al, (), Abdel‐Khalek, El‐Nagar, and Omima (), Kapadiya, Nakhashi, Sutaria, Rathod, and Suthar (), Pang et al, (), Asma‐ul‐Husna et al, () in bulls; Perumal, Vupru, and Khate (), Perumal et al, (), Perumal, Chang, Sangma, Savino, and Khate (), Perumal, Baruah, et al () in Mithun at 5°C; Ashrafi, Kohram, Naijian, Bahreini, and Poorhamdollah (), Succu et al, (), Casao et al, () in rams; Balao da Silva et al, () in stallions at 37°C; Izadpanah, Zare‐Shahneh, Zhandi, Yousefian, and Emamverdi () in stallions at 5°C and El‐Battawy and El‐Nattat () in goats; who reported that the addition of melatonin to semen freezing extender could protect the spermatozoa from damage during cryopreservation and improve the post‐thaw semen quality.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The data obtained regarding sperm motility are in accordance with Ashrafi et al, (), Cheuqueman et al, (), Abdel‐Khalek, El‐Nagar, and Omima (), Kapadiya, Nakhashi, Sutaria, Rathod, and Suthar (), Pang et al, (), Asma‐ul‐Husna et al, () in bulls; Perumal, Vupru, and Khate (), Perumal et al, (), Perumal, Chang, Sangma, Savino, and Khate (), Perumal, Baruah, et al () in Mithun at 5°C; Ashrafi, Kohram, Naijian, Bahreini, and Poorhamdollah (), Succu et al, (), Casao et al, () in rams; Balao da Silva et al, () in stallions at 37°C; Izadpanah, Zare‐Shahneh, Zhandi, Yousefian, and Emamverdi () in stallions at 5°C and El‐Battawy and El‐Nattat () in goats; who reported that the addition of melatonin to semen freezing extender could protect the spermatozoa from damage during cryopreservation and improve the post‐thaw semen quality.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, supplementation of melatonin as a potent antioxidant has been implicit either througout cryopreservation of semen (Zhao et al, ). More specifically, melatonin can directly benefit sperm characteristics, together with increased total motility, progressive motility, and viability rate enhanced sperm membrane and DNA integrity reduced membrane lipid peroxidation and modulation of sperm capacitation (Pang et al, ). The effect of melatonin on bovine spermatozoa remains arguable (Ashrafi, Kohram, & Ardabili, ) and therefore underlying mechanism has not nevertheless been well elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mice treated with different antioxidants for 12 months had substantial increases in litter size, pool of follicles, and telomere length as well as oocyte quantity and quality . Many studies have reported the protective effects of melatonin on oxidative stress; especially, melatonin treatment improved the quality of the oocytes, promoted the embryo development pregnant rate, and increased the numbers of the offspring in different species . It has been found that melatonin was present in porcine follicular fluid which improved in vitro maturation and parthenogenetic development of porcine oocytes .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the protective effects of melatonin on oxidative stress 21,47 ; especially, melatonin treatment improved the quality of the oocytes, 19 promoted the embryo development pregnant rate, 48 and increased the numbers of the offspring in different species. 56 It has been found that melatonin was present in porcine follicular fluid which improved in vitro maturation and parthenogenetic development of porcine oocytes. 57 When porcine oocytes under heat stress, supplementing melatonin protected oocytes and improved in vitro maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it increases the blastocyst rate and it decreases apoptosis rate. [75] Human Blastocyst 10 -7 M in culture system in 3D (Encapsulation) Increases the survival time of encapsulated embryos. [76] Bovine Oocytes 10 -6 or 10 -9 M for 24 hours during in vitro maturation In cumulus cells, it up-regulates MnSOD and Cu-ZnSOD.…”
Section: Melatoninmentioning
confidence: 99%